A Comparative Study on Current Thai Graduates’ Performance and their Employers’ Expectation in Nakhon Si Thammarat - Wimonchong, Pornnapat (JOURNAL OF SOUTHERN TECHNOLOGY, 2021)
The present study is aimed to investigate and compare the current Thai graduates’ performance at work with those of their respective employers’ expectations. The studies focused on 5 aspects of graduate skills including knowledge skills, job performance, personality traits, leadership skills, and ethical conducts. The data of this research were collected from 368 executive managers, supervisor and business owners from the government sectors and private sectors in Nakhon Si Thammarat province. The result indicated that Thai graduates personality traits were rated highest, followed by their ethical conducts, knowledge skills, leadership skills and job performance, respectively. The employers on the other hand, expect that the Thai graduates should be in their order of importance excel in ethical conducts, knowledge skills, job performance, personality traits and leadership skills, respectively. The discrepancy between the Thai graduate skills and their organizational expectation was found to be statistically significant in all the 5 studied aspects.